Alternativas Metodológicas para a Identificação de Competências - Queiroz Barbosa, Allan Claudius; Rodrigues, Marco Aurélio (Boletim Técnico do Senac, 2006)
This article examines the origin of the “competence approach” in the field of studies of organization, labor, and strategy, as a response to increasing environmental turbulences and uncertainties. It describes and compares the distinctive characteristics of some of the main methodological approaches that have been suggested to identify and build systems for managing people through competences.